2009
DOI: 10.1016/j.envres.2009.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in fetal growth of newborns exposed prenatally to airborne fine particulate matter

Abstract: Our primary purpose was to assess sex-specific fetal growth reduction in newborns exposed prenatally to fine particulate matter. Only women 18–35 years of age, who claimed to be non-smokers, with singleton pregnancies, without illicit drug use and HIV infection, free from chronic diseases were eligible for the study. A total of 481 enrolled pregnant women who gave birth between 37 and 43 weeks of gestation were included in the study. Prenatal personal exposure to fine particles over 48 h during the second trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
2
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 64 publications
(67 reference statements)
9
67
2
5
Order By: Relevance
“…Few studies have explored the biological pathways that might explain the greater susceptibility of male fetuses to air pollution (Clougherty, 2010;Jedrychowski et al, 2009). A recent study has suggested that they may be more vulnerable than females to maternal oxidative stress (Minghetti et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Few studies have explored the biological pathways that might explain the greater susceptibility of male fetuses to air pollution (Clougherty, 2010;Jedrychowski et al, 2009). A recent study has suggested that they may be more vulnerable than females to maternal oxidative stress (Minghetti et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, growing evidence suggests these mechanisms may differ according to the fetus's sex (Bolton et al, 2014). Sex-linked traits (e.g., hormonal status and body size) influence both biological responses to exposure to environmental toxicants and the biological transport of these environmentally derived chemicals (Clougherty, 2010), and male newborns are suggested to be more vulnerable to prenatal exposure to air pollution (Jedrychowski et al, 2009;Ghosh et al, 2007;Lakshmanan et al, 2015). Because these biological differences in toxicology begin at the embryo stage, it appears necessary to assess sex-specific air pollution effects on fetal growth.…”
Section: Introductionmentioning
confidence: 99%
“…In another study conducted in southern Sweden Downloaded by [University of Chicago Library] at 10:34 08 December 2014 Ambient Air Pollution and Birth Outcomes: An Overview 755 no correlation was observed between the various environmental pollutants, such as SO 2 and NO, and PTD or LBW (Landgren, 1996). Furthermore, other researches have shown that air pollution exposure may induce toxic effects more frequently on female fetuses compared to male fetuses , while in another research the opposite result has been observed (Jedrychowski et al, 2009). Conflicting data have been also reported as regards the role of pregnancy time, in particular considering the exposure during the first, mid, and last trimester or the whole period (Bell et al, 2007;Bobak, 2000;Wang et al, 1997).…”
Section: Introductionmentioning
confidence: 80%
“…By contrast only recently, the scientific community has addressed studies regarding the possible effects of environmental pollutants on pregnant women health and birth outcomes. These studies have been performed by the association between AAP exposure and the appearance of many diseases affecting fetal development, such as preterm birth delivery (PTD, <37 weeks), low birth weight (LBW, <2500 g), very low birth weight (VLBW, <1500 g), intrauterine growth restriction (IUGR), intrauterine mortality (IUM), congenital anomalies (CA; Figure 1; Dejmek et al, 1999;Gray et al, 2009;Ha et al, 2001;Hansen et al, 2006;Jedrychowski et al, 2009;Leem et al, 2006;Liu et al, 2003;Llop et al, 2010;Maisonet et al, 2001;Maroziene and Grazuleviciene, 2002;Morello-Frosch et al, 2010;Ritz et al, 2007;Rogers and Dunlop, 2006;Salam et al, 2005;Wu et al, 2009;Yang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, little has been done to examine the potential modifiers of the health effects of air pollution on birth outcomes. Limited evidence suggests that the effect sizes of air pollution on adverse pregnancy outcomes may be different by fetal gender Jedrychowski et al 2009), pregnancy complication (Rich et al 2009), and maternal nutrition (Jedrychowski et al 2007;Kannan et al 2006). Much remains to be learned about these relationships and what else could cause fetuses to be especially sensitive to the adverse health effects of air pollution.…”
Section: Recommendations Of Future Studiesmentioning
confidence: 99%